The relation between stakeholders' integration and environmental competitiveness. Issue 4 (3rd October 2016) - Salem, Milad Abdelnabi; Shawtari, Fekri Ali; Shamsudin, Mohd Farid; Hussain, Hafezali Iqbal
Abstract : Purpose: This paper aims to explain the relationships between three dimensions of stakeholders' integration and competitiveness focusing on 226 industrial corporations. It aims to investigate the influences of stakeholders' integration on three dimensions of competitiveness. Design/methodology/approach: The study adopts a cross-sectional study using a self-reported questionnaire. The collected data are analysed using structural equation modelling technique based on AMOS. Findings: The results revealed that knowledge of the stakeholders per se will not provide any contribution to the different dimensions of competitiveness. Companies should extend their focus to adapt behaviours in line with stakeholders' interests to gain competitive advantages. The data showed that in line with the stakeholders' theory concept, adaptive behaviour dimension positively affects the three dimensions of competitiveness. Research limitations/implications: There are several limitations that should be taken into consideration. First, the study used a self-reported questionnaire filled in by managers in the study sample; therefore, survey data might be subject to social desirability bias. Second, this study was conducted in Libya, which is considered a developing country, and, thus, caution should be taken when generalizing the results of the study. Originality/value: To date, there is no an empirical evidence on how environmental stakeholders' integration might affect firm competitiveness. Previous literature has investigated this issue using different environmental practices. However, none have used stakeholders' integration in the environmental domain as a predictor to competitiveness. Therefore, the paper contributes to the body of knowledge by stating and testing the potential contributions of stakeholders' integration to the multidimensional approach of competitiveness.